Sero-prevalence of brucellosis in sheep and springbok (Antidorcas marsupialis) in the Karas Region of Namibia - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2013.